Refractive and Quality of Vision Outcomes with Toric IOL Implantation in Low Astigmatism - Eduardo Scaldini Buscacio; Lia Florim Patrão; Haroldo Vieira de Moraes (Journal of Ophthalmology)
Purpose. To evaluate the refractive and the quality of vision outcomes of toric IOL implantation in patients with low astigmatism. Design. Prospective study of single-arm. Methods. Patients with corneal astigmatism range from 0,75 D to 1,5 D and cataract that underwent cataract surgery with toric IOL. The measurements were performed preoperatively and 6 weeks after the surgery. Patients were evaluated for visual acuity with and without correction, contrast sensitivity, static and dynamic refraction, and quality of life questionnaire. Pre- and postoperative values were compared and their variations were evaluated for linear correlation. Results. 21 eyes of 21 patients. Postoperative mean uncorrected visual acuity was 0.80±0.19, and the best corrected visual acuity was 0.97±0.15. p<0.001 compared to preoperative values. The average postoperative refractive cylinder was -0.34±0.39. The questionnaire’s total value before and after surgery was, respectively, 43.20±15.76 and 79.70±10.11 (p<0.001). The correlation coefficients between the values of the questionnaire variation and the UCVA, BCVA, and CS variation were, respectively, 0.548 (p=0.005), 0.508 (p=0.009), and 0.409 (p=0.033). Conclusion. Patients with low astigmatism who underwent phacoemulsification with toric IOL implantation experienced significant decrease in refractive astigmatism and improvement in their quality of life.